Numerical efficiency calibration of in vivo measurement systems : Monte Carlo simulations of in vivo measurement scenarios for the detection of incorporated radionuclides, including validation, analysis of efficiency-sensitive parameters and customized anthropomorphic voxel models - Hegenbart, Lars (KIT Scientific Publishing, 2010)
Monte Carlo radiation transport codes were used with virtual models of in vivo measurement equipment. Software was coded to handle memory intensive anthropomorphic voxel models for simulation of measurement scenarios. Tools, methods and models have been validated. Various parameters have been investigated for their sensitivity. Methods based on image registration techniques have been developed to transform existing human models to match with an individual test person.